Framework for Business Technology and Innovation at the Bottom of the Pyramid - Fu, Ching Yee (2008)
Businesses are directly impacted by world socioeconomic, political and climatic trends. As globalization accelerates, the case for incorporating awareness and action on these issues into corporate strategy become overwhelmingly strong. If businesses mishandle or ignore global issues ranging from poverty to climate change, it can potentially cause severe financial and reputation damage. Responding to these problems can generate economic opportunities in new markets. The four billion people at the Bottom of the Economic Pyramid live on $2 a day or less, but collectively represent a $5 trillion global market that is significantly underserved. Several authors on the subject proposed strategies that will help companies succeed at entering this new market segment, by simultaneously generating profits, achieving sustainability and creating new sources of innovation. One key element in these strategies is the use of disruptive innovation and technology. However, innovation and technology alone is rarely the key to unlocking economic value. Organizations need to execute a balanced strategy that combines various elements in order to be successful. In this report, the Framework for Business Technology and Innovation was theorized, outlining the three main components that are necessary to the successful implementation of innovation and technology for the BOP markets. Three cases of social enterprises operating in three different industries and locations were analyzed based on this framework, proving that the framework is applicable and valid in determining the factors of success for innovation and technology at the BOP. Companies must have a business model targeted at the BOP market, utilize C.K. Prahalad’s 12 principles to design disruptively innovative offerings and form a supportive ecosystem of partnerships and relationships.